Shariah supervisory board attributes and corporate risk-taking in Islamic banks - Hasan Mukhibad; Doddy Setiawan (Cogent Business & Management, 2022)
Previous studies use mainly insolvency, credit, liquidity, market, and operational risk to measure risk-taking in Islamic banks. We are expanding the risk indicators: credit risk, market risk, liquidity risk, operational risk, legal risk, reputation risk, strategic risk, shariah compliance risk, rate of return risk, equity investment risk, and insolvency risk. We summarize these risks in a risk index. Additionally, we expanded the Shariah Supervisory Board (SSB) attribute indicator and developed the SSB busyness attribute unused by previous researchers. The study sample included 14 Islamic commercial banks in Indonesia, observed from 2010 to 2020. Fixed effect and random effect data analysis models were used. Model determination is based on Hausman test results. Based on the test results for each type of risk, we find that busyness, educational background (economics/finance and Islamic law), and SSB experience has a negative effect on the risk. However, SSB's level of education encourages directors to take risks. This result is also consistent when using a risk index where SSB education can increase the risk. Our findings strengthen the resources-dependent theory that experience, busyness, and educational background as access to resources have an impact on increasing the knowledge and skills of SSB in controlling risk. The findings are robust to the potential issues of endogeneity and sensitivity analyses.
Keywords: 650; education; experience; busyness; risk taking; shariah compliance risk; tenure